+0  
 
0
504
3
avatar

simplify the square root of 8 times the square root of 6 times the square root of 3.

Guest Feb 22, 2017
 #1
avatar+7155 
+1

\((\sqrt{8})(\sqrt{6})(\sqrt{3})\)

\(= \sqrt{(8)(6)(3)}\)

\(= \sqrt{(2)(2)(2)(2)(3)(3)}\)

\(= (\sqrt{(2)(2)})(\sqrt{(2)(2)})(\sqrt{(3)(3)})\)

\(= (2)(2)(3)\)

\(= 12\)

hectictar  Feb 22, 2017
 #2
avatar+12565 
0

Nice job hecticar....here is another way

sqrt 8  sqrt 6  sqrt 3  = sqrt(8*6*3) = sqrt(144) = 12

ElectricPavlov  Feb 22, 2017
 #3
avatar+7155 
+1

True...I was overthinking it a little haha.

hectictar  Feb 22, 2017

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.